Novel sweep-type triboelectric nanogenerator utilizing single freewheel for random triggering motion energy harvesting and driver habits monitoring. (February 2020) - Xie, Zhijie; Zeng, Zhenghui; Wang, Yuqi; Yang, Weixiong; Xu, Yuhong; Lu, Xiaohui; Cheng, Tinghai; Zhao, Hongwei; Wang, Zhong Lin
Abstract: Traffic safety has always been a social concern, and driver habits directly affect traffic safety. Therefore it is significant to monitor driver habits. The pedal is the core operating device in the process of driving, so increasingly importance has been attached to the step movement of driver. The triboelectric nanogenerators (TENGs) performs well in harvesting the energy of random triggering motion and reflecting the characteristics of random triggering motion. This reports a novel sweep-type triboelectric nanogenerator (ST-TENG), which consists of a push rod, shells, two flywheels and a single freewheel. ST-TENG can harvest the energy of random triggering motion and monitor driver habits. Experiments show that the ST-TENG can generate the open-circuit voltage is 400 V and the short-circuit current is 15 μA, and it is found that ST-TENG data could be exploited to reflect road conditions and driver habits. And ST-TENG has the potential to popularize intelligent driving systems. Graphical abstract: Image 1 Highlights: A novel sweep-type triboelectric nanogenerator (ST-TENG) is proposed to harvest the energy of random triggering motion. The ST-TENG can generate the open-circuit voltage is 400 V and the short-circuit current is 15 μA. The Fast Fourier Transformation (FFT) is adopted to process the voltage signal of ST-TENG to reflect driving habits.